Rekonstruksi Tafsir Tematik tentang Poligami dalam Al-Qur’an: Telaah Keadilan melalui QS An-Nisa Ayat 3 dan 129 - Milawati, Milawati; Mardan, Mardan; Yusuf, Muhammad (JENTRE, 2025)
This article aims to explore the concept of polygamy in the Qur’an through the method of tafsir maudhū‘i (thematic exegesis), focusing on QS An-Nisa: 3 and QS An-Nisa: 129. The thematic approach collects and interprets Qur’anic verses related to polygamy as a unified discourse. Primary data were drawn from the Qur’an, while secondary data  included classical and contemporary tafsir literature. The findings reveal that the Qur’an does not advocate polygamyas a normative practice but allows it under strict conditions, particularly the principle of justice. Moreover, the Qur’an acknowledges the inherent difficulty in maintaining emotional fairness.Thus, favoring monogamy is more aligned with the Islamic ideal of justice. The study concludes that justice is the ethical foundation of marital relationships in the Qur’an, and polygamy must be interpreted within this moral framework. It recommends a holistic and contextual reading of the Qur’anic verses to prevent reductionist interpretations of women and marriage in Islam.